A 10-bit 300-MS/s asynchronous SAR ADC with strategy of optimizing settling time for capacitive DAC in 65 nm CMOS. Issue 10 (October 2015) - Liang, Yuhua; Zhu, Zhangming; Ding, Ruixue
Abstract A 10-bit 300-MS/s asynchronous SAR ADC in 65 nm CMOS is presented in this paper. To achieve low power, binary-weighed capacitive DAC is employed without any digital correction or calibration. Consequently, settling time for the capacitive DAC would be a dominant limiting factor for the ADC operating speed. A novel architecture is proposed to optimize the settling time for the capacitive DAC, which depends merely on the on-resistance of switches and the capacitance of unit capacitor and irrelevant to the resolution. Therefore, high-speed high-resolution SAR ADC is possible. What is deserved to highlight is that the architecture improves the ADC performance at a fraction of the cost, with only some capacitors and control logic added. Post-layout simulation has been made for the SAR ADC. At a 1.2-V supply voltage and a sampling rate of 300 MS/s, it consumes 1.27 mW and achieves an SNDR of 60 dB, an SFDR of 67.5 dB, with the Nyquist input. The SAR ADC occupies a core area of 450×380 μm2.